Diabetic candy, cookie & dessert cookbook - Finsand, Mary Jane. frey50 (New York : Sterling Pub. Co., 1982)
Chemist-nutritionist Mary Jane Finsand has created over two hundred recipes you can make using sugar replacements, each listing ingredients in customary and metric measurements.
Includes index.
Keywords: Diabetes -- Diet therapy; Confectionery; Desserts; Diet, Diabetic; Popular Works; Recipes